Discovered outdoors: typification of names of taxa described from Italy outside their native range - Ardenghi, Nicola M.g.; Galasso, Gabriele; Banfi, Enrico (Phytotaxa, 2015)
Between the 18th and the early 20th century, a number of naturalized neophytes were described in Europe, outside their area of origin. Although most of the names of these taxa, discovered in a period without fast computer-mediated communication and world-wide electronic availability of taxonomic papers, today are treated as synonyms, their existence allows to shed light on a peculiar taxonomic phenomenon connected to the early stages of the European alien flora studies. In this paper we select two lectotypes and one neotype for three neophytes described in Italy, belonging to the critical graminoid genera Cyperus (C. aristatus var. boeckeleri), Echinochloa (Panicum erectum), and Eleocharis (Scirpus erraticus). The selected types are conserved at PAV-Erbario Lombardo and RO.